P-I Diagram Generation for Reinforced Concrete (RC) Columns Under High Impulsive Loads Using Ale Method - Abedini, Masoud; Mutalib, Azrul A; Raman, Sudharshan N (Journal of Asian Scientific Research, 2017)
Reinforced concrete (RC) column systems are widely used in protective structures designed to resist blast events. Development of correlations between explosive load and the resulting damage in concrete elements are significant for incorporation of blast load in design and also for pre and post-damage assessments. The main purpose of this research is to organizing correlations between explosive load and damage. These correlations are being expressed in Pressure-Impulse diagrams. The damage level is calculated based on the residual axial load-carrying capacity of the damaged RC column. Finite element modeling in LS-DYNA is used to analyze the structures and calculate the damage level for each explosive phenomenon. The Arbitrary Lagrangian Eulerian (ALE) method is used to simulate the explosive loads in the reinforced concrete column. The results demonstrated that increase the column size cause to increase in pressure and impulsive asymptotes and lead to enhanced the pressure-impulse (P-I) diagram.